Clinical evaluation of packable resin Class I restorations after 7 years - João Batista Novaes Junior; Patrícia Valente Araújo; Fernanda Damas; Alfonso Gala-Garcia; Maria Esperanza Cortés (Universidade Estadual de Campinas, 2008)
Aims: Compactable composite resins have been indicated as amalgam substitutes. However, longitudinal clinical trials are necessary to verify their wear resistance and integrity maintenance. The purpose of this study was to evaluate the clinical performance of a packable resin in Class I restorations after 7 years. Methods: Forty restorations were placed in 15 young patients aged 13 to 30 years. The restorative material (Prodigy/OptiBond-KERRâ ) was used according to standard recommendations. The restorations were assessed at baseline at the year 2000 and after 2 and 7 years according to the USPHS (United State Public Health Service) criteria. Results: After 7 years, 50% of the restorations were scored Alpha and 37.5% scored Bravo for color match, marginal discoloration and marginal adaptation. Secondary caries were observed in only one restoration and none of them presented postoperative sensibility. Conclusion: In accordance with the USPHS method used, the packable resin presented appropriate clinical performance after a 7-year clinical evaluation.